Providing a Model for the Development of Adjunct Faculty Collaboration in the Islamic Azad University - Qezelsefloo, Ali; Arasteh, Hamidreza; Zamani Moghadam, Afsaneh (Iranian Journal of Educational Sociology, 2022)
Purpose: The primary objective of this study was to develop a comprehensive model to enhance adjunct faculty collaboration at Islamic Azad University. The research focused on identifying key factors influencing adjunct faculty collaboration by exploring professional, organizational, and individual competencies. Methods and Materials: This study used a quantitative, descriptive-survey research design. The statistical population comprised all adjunct faculty members at Islamic Azad University, with a sample of 404 participants selected using multi-stage cluster random sampling, calculated through Cochran's formula. A researcher-made questionnaire with 95 items across three dimensions—professional competencies, organizational competencies, and individual competencies—was used for data collection. The reliability of the questionnaire was confirmed with a Cronbach’s alpha of 0.7. Data were analyzed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to validate the proposed model. Findings: The results from EFA identified 12 key factors across the three dimensions, including service delivery skills, job commitment, teaching technology, scientific production, educational innovation, self-efficacy, job identity, foresight, service to society, organizational ethics, participation in scientific development, and support and backing. The CFA confirmed these findings, with self-efficacy and teaching technology emerging as the most significant factors within individual and professional competencies, respectively. The R² values indicated strong correlations between the identified factors and adjunct faculty collaboration. Conclusion: The study provides a comprehensive model for improving adjunct faculty collaboration, emphasizing the importance of institutional support, professional development, and engagement in scientific activities. Universities can enhance adjunct faculty engagement by focusing on the key competencies identified, fostering a supportive academic environment that promotes collaboration and innovation.